Recent progress in terahertz metamaterial modulators - Degl’Innocenti Riccardo; Lin Hungyen; Navarro-Cía Miguel (Nanophotonics)
The terahertz (0.1–10 THz) range represents a fast-evolving research and industrial field. The great interest for this portion of the electromagnetic spectrum, which lies between the photonics and the electronics ranges, stems from the unique and disruptive sectors where this radiation finds applications in, such as spectroscopy, quantum electronics, sensing and wireless communications beyond 5G. Engineering the propagation of terahertz light has always proved to be an intrinsically difficult task and for a long time it has been the bottleneck hindering the full exploitation of the terahertz spectrum. Amongst the different approaches that have been proposed so far for terahertz signal manipulation, the implementation of metamaterials has proved to be the most successful one, owing to the relative ease of realisation, high efficiency and spectral versatility. In this review, we present the latest developments in terahertz modulators based on metamaterials, while highlighting a few selected key applications in sensing, wireless communications and quantum electronics, which have particularly benefitted from these developments.